PERAN MODAL INTELEKTUAL TERHADAP KINERJA UMKM: SUATU TINJAUAN SISTEMATIS - Vitalis Ari Widiyaningsih; Bambang Sutopo (JURNAL ILMIAH EDUNOMIKA, 2025)
Global challenges require Micro, Small, and Medium Enterprises (MSMEs) to adopt adaptive strategies to achieve competitive advantage. Intellectual Capital (IC) is viewed as a strategic resource capable of improving MSME operational performance. However, the relationship between Intellectual Capital and MSME performance is complex because it is influenced by various mediating and moderating factors. This study aims to identify and synthesize the mediating and moderating mechanisms that influence the relationship between Intellectual Capital and MSME performance. The method used is a Systematic Literature Review (SLR) by analyzing 20 scientific articles published in the 2020–2024 period, sourced from the Scopus and Google Scholar databases. The analysis process was carried out systematically to examine variables that act as mediators and moderators in the relationship between Intellectual Capital and MSME performance. The results show that Intellectual Capital contributes significantly to improving MSME performance, but its effect depends on the intermediary variable. Knowledge Management (KM) and innovation capability were identified as the main mediators that strengthen the influence of Intellectual Capital on performance. Meanwhile, environmental dynamics and debt financing act as moderators that can weaken or strengthen this relationship. Furthermore, organizational culture was also found to be a crucial element influencing the effectiveness of Intellectual Capital implementation. Overall, these findings underscore the need for a holistic and contextual approach to Intellectual Capital management in MSMEs. Integrating KM practices, organizational learning capacity, and a comprehensive assessment of MSMEs' internal and external conditions are key to maximizing the contribution of Intellectual Capital to sustainable performance. Keywords: Intellectual Capital; UMKM, Performance; Systematic Literature Review; Knowledge Management   Keywords: Intellectual Capital, UMKM, Performance, SLR